Enhancing stakeholder engagement in sustainable forest management: A multi‐domain comparative analysis of forest‐related beliefs, values, and behaviors of Canadian Aboriginal and non‐Aboriginal groups - Yiwen, Zhang; Kant, Shashi; Vertinsky, Ilan (Sustainable development (Bradford, West Yorkshire, England), 2024)
The study aims to understand the variations in the domain‐specific pro‐sustainable‐forest‐management behavior (PSFMBs) and their explanatory factors across ecological, economic, recreational, and Aboriginal domains and between Aboriginal and non‐Aboriginal groups. A hybrid model of PSFMB, which integrates environmental psychology and resource economics perspectives, is conceptualized and estimated using multi‐group path analysis and data from three Aboriginal and three non‐Aboriginal communities in Ontario, Canada. Results show that both groups make substantial pro‐SFM contributions, but the contributions and their influencing factors differ across domains and groups. For Aboriginals, environmental worldviews and assigned forest values are the only influencing factors, while for non‐Aboriginals, income and forest environmental conditions play dominant roles. The findings confirm the fundamental differences in the roles of beliefs, values, and situational factors in influencing the PSFMB of Aboriginal and non‐Aboriginal groups, highlight the need for theoretical lenses that account for cultural differences, and contribute to the development of inclusive policies that respect the unique values of different social groups.